Simplify the expression 3y(2y-7)-3(y-4) for y = -3

Question

Simplify the expression 3y(2y-7)-3(y-4) for y = -3

in progress 0
Josie 1 month 2021-09-22T22:23:32+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-09-22T22:24:44+00:00

    Step-by-step explanation:

    Given that:

    3y(2y-7)-3(y-4) for y = -3

    To find: Simplification of expression

    Solution:

    For simplification of expression,for y=-3

    put the value of y in expression

    3y(2y - 7) - 3(y - 4) \\  \\  = 3( -3 )(2 \times ( - 3) - 7) - 3( - 3 - 4) \\  \\  =  - 9( - 6 - 7) - 3( - 7) \\  \\  =  - 9( - 13) + 21 \\  \\  = 117 + 21 \\  \\  = 138 \\  \\

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )